Facial expression classification based on MPEG-4 FAPs: the use of evidence and prior knowledge for uncertainty removal - Wallace, Manolis; Raouzaiou, Amaryllis; Tsapatsoulis, Nicolas; Kollias, Stefanos D. (My University, 2004)
As low resolution shots, rotations of the head with respect to the camera, face deformation due to speech and so on inflict a great deal of uncertainty in FAP measurements, uncertainty is also inherent in the process of expression analysis. We tackle such uncertainty via the observation that user emotions do not typically alter rapidly very often. Thus, possibilistic evidence may be gathered from each frame about the user expression; evidence from the current and recent frames can be combined using evidence theory
Keywords: Fuzzy systems; Facial expression; Face--Identification; Linguistics; Neural networks